Bi-Directional Shield Recovery in a Wide Face Longwall Move with a Pre-Driven Recovery Room under Weak Roof Conditions - Peter Zhang (International Conference on Ground Control in Mining, 2007)
Shield recovery in a longwall move is normally conducted from tailgate to headgate. However, if the face is wide and the immediate roof is weak, difficult conditions with considerable roof sag, excessive shield load, and local roof falls could occur as the shield recovery proceeds to the middle of the face, causing delays in shield recovery. The situation could be aggravated when a pre-driven longwall recovery room is employed. Alternatively, a bi-directional approach for shield recovery, i.e. shield recovery starting from the middle of the face towards both tailgate and headgate, can alleviate the roof sag significantly by quickly withdrawing the shields towards the lower abutment pressure zones at the headgate and tailgate sides. In this case, the bi-directional shield recovery approach was used in a longwall move for a 1450 ft wide face under weak roof conditions. Shields were successfully withdrawn within five days without experiencing significant roof sag. The time-dependent roof-to-floor convergence, shield pressure, and roof conditions were monitored during shield recovery. 3-D finite element modeling was conducted prior to longwall move to evaluate the difference between a uni-directional and a bi-directional shield recovery during a longwall face move. Vertical stress, yield zone in and around the recovery room, load on the shields, and convergence at the center of the shield canopy were obtained from computer modeling, and compared with the data from field monitoring. Finally, the advantages of the bi-directional shield recovery are discussed.